Effects of high-intensity intermittent training on carnitine palmitoyl transferase activity in the gastrocnemius muscle of rats - Carnevali Jr,L.C. (2012)
We examined the capacity of high-intensity intermittent training (HI-IT) to facilitate the delivery of lipids to enzymes responsible for oxidation, a task performed by the carnitine palmitoyl transferase (CPT) system in the rat gastrocnemius muscle. Male adult Wistar rats (160-250 g) were randomly distributed into 3 groups: sedentary (Sed, N = 5), HI-IT (N = 10), and moderate-intensity continuous training (MI-CT, N = 10). The trained groups were exercised for 8 weeks with a 10% (HI-IT) and a 5% (MI-CT) overload. The HI-IT group presented 11.8% decreased weight gain compared to the Sed group. The maximal activities of CPT-I, CPT-II, and citrate synthase were all increased in the HI-IT group compared to the Sed group (P < 0.01), as also was gene expression, measured by RT-PCR, of fatty acid binding protein (FABP; P < 0.01) and lipoprotein lipase (LPL; P < 0.05). Lactate dehydrogenase also presented a higher maximal activity (nmol·min-1·mg protein-1) in HI-IT (around 83%). We suggest that 8 weeks of HI-IT enhance mitochondrial lipid transport capacity thus facilitating the oxidation process in the gastrocnemius muscle. This adaptation may also be associated with the decrease in weight gain observed in the animals and was concomitant to a higher gene expression of both FABP and LPL in HI-IT, suggesting that intermittent exercise is a "time-efficient" strategy inducing metabolic adaptation.